A case with Gianotti-Crosti syndrome with a history of atopic dermatitis: Gianotti-Crosti syndrome with a history of atopic dermatitis - Oktay, Mehmet Ali; Oktay, Selin Akyüz (Journal of Surgery and Medicine, 2024)
Gianotti-Crosti syndrome (GCS) is characterized by the sudden onset of a papular or papulovesicular rash with a symmetrical distribution. This rash mainly appears on the extensor surfaces of the limbs, buttocks, and face. GCS is most frequently observed in children aged 1 to 6 years. In this case, we present the diagnosis of GCS in an 8-month-old male patient who also has a history of atopic dermatitis. Symmetrical, multiple, monomorphic, raised, red, and itchy lesions were identified on the patient’s face, trunk, arms, and legs. The presence of atopic dermatitis was notably more common in individuals with GCS, suggesting a significant association with a family history of atopy. GCS is a syndrome that demands a high degree of clinical suspicion as it can be mistaken for other childhood exanthematous diseases.